Safety, efficacy, and immunogenicity of COVAXIN: A review - Mukhtar Ahmad Dar, Priyadarshani Chauhan, Pawan Kumar, Richa Chauhan, Krishna Murti, Jaykaran Charan, Velayutham Ravichandiran, Sameer Dhingra (Journal of Applied Pharmaceutical Science, 2021)
COVAXIN was granted restricted emergency approval based on safety and immunogenicity studies alone. The approval was heavily questioned leading to controversy regarding safety concerns and unethical trial allegations resulting in lack of trust and vaccine hesitancy among common people. In this article, we aimed to review the scientific evidence regarding the safety and immunogenicity of COVAXIN. Adverse events reported in phase-I/II COVAXIN trials were mild to moderate with no serious adverse events. The incidence of adverse events due to COVAXIN was comparable to other inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines like BBIBP-CorV and CoronaVac. COVAXIN has also demonstrated a similar immunogenicity profile and enhanced immune response as reported by other inactivated vaccines. COVAXIN has demonstrated an enhanced humoral and cell-mediated immune response among vaccine recipients. COVAXIN vaccinated human serum has also shown comparable antibody neutralization activity against SARS-CoV-2 variant B.1.1.7, B.1.617, and other heterologous strains. Evidence suggests that COVAXIN is a safe, well-tolerated, and immunogenic coronavirus disease 2019 vaccine. Its stated efficacy of 77.8% significantly exceeds the World Health Organization’s recommendations. However, the COVAXIN phase-III clinical trial data need to be peer reviewed for better transparency and building public confidence in indigenously developed vaccine and shedding COVAXIN hesitancy among common masses.
Keywords: SARS-CoV-2, COVID-19, COVAXIN, safety, immunogenicity, efficacy.